KINESTHETIC AND VISUAL IMAGERY IN YOUNG ADULTS WITH CHRONIC NECK PAIN: English - Ozcan, Ozlem; Kul Karaali, Hayriye (Sanamed, 2022)
Background:Young adults complain of neck pain almost every year. In recent years the ability of motor imagery (kinesthetic and visual imagery) in many musculoskeletal system problems other than neck pain in young adults has been investigated in the literature. The Cross-Sectional study aimed to question motor imagery ability in young adults with chronic neck pain. Methods: Two groups were included in the study: the chronic neck pain group (n = 83) and the control group (n = 91). Motor imagery ability of both groups was evaluated with Movement Imagery Questionnaire-3. Additionally, in the chronic neck pain group, pain was evaluated with the Short Form-McGill Pain Questionnaire, disability was evaluated with the Neck Disability Index, and kinesiophobia was evaluated with Tampa Scale for Kinesiophobia. Conclusions: Internal visual imagery and kinesthetic imagery were significantly different between chronic neck pain and control groups. There was a negative linear relationship between disability and internal visual imagery, external visual imagery, and kinesthetic imagery. Motor imagery ability is reduced in young adults with chronic neck pain. In addition, as the severity of disability increases, the motor imagery ability decreases. Therefore, it is considered appropriate to include a motor imagery training program when treating chronic neck pain in the future.